2014
DOI: 10.1111/jnc.12973
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nesfatin‐1 in the paraventricular nucleus on gastric motility and its potential regulation by the lateral hypothalamic area in rats

Abstract: The current study investigated the effects of nesfatin-1 in the hypothalamic paraventricular nucleus (PVN) on gastric motility and the regulation of the lateral hypothalamic area (LHA). Using single unit recordings in the PVN, we show that nesfatin-1 inhibited the majority of the gastric distention (GD)-excitatory neurons and excited more than half of the GD-inhibitory (GD-I) neurons in the PVN, which were weakened by oxytocin receptor antagonist H4928. Gastric motility experiments showed that administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
4
21
0
1
Order By: Relevance
“…In this study, the prominent immunoexpression of NUCB2/nesfatin-1 in the PVN, SON, IFN, and LHA is in agreement with neuroanatomical evidence and functional analyses from animal studies, revealing that NUCB2/nesfatin-1 effects on energy homeostasis are primarily mediated by PVN, SON, Arc (IFN), and LHA NUCB2/nesfatin-1 [3, 5-10, 21, 29-31, 33, 42-44]. NUCB2/nesfatin-1 localization pattern in human hypothalamic nuclei is indicative of a potential function for NUCB2/nesfatin-1 as an integral regulator of energy homeostasis; moreover, it could imply a role for NUCB2/nesfatin-1 in the regulation of other neuroendocrine and autonomic functions, which will require further studies in humans.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, the prominent immunoexpression of NUCB2/nesfatin-1 in the PVN, SON, IFN, and LHA is in agreement with neuroanatomical evidence and functional analyses from animal studies, revealing that NUCB2/nesfatin-1 effects on energy homeostasis are primarily mediated by PVN, SON, Arc (IFN), and LHA NUCB2/nesfatin-1 [3, 5-10, 21, 29-31, 33, 42-44]. NUCB2/nesfatin-1 localization pattern in human hypothalamic nuclei is indicative of a potential function for NUCB2/nesfatin-1 as an integral regulator of energy homeostasis; moreover, it could imply a role for NUCB2/nesfatin-1 in the regulation of other neuroendocrine and autonomic functions, which will require further studies in humans.…”
Section: Discussionsupporting
confidence: 67%
“…When administered into the PVN, nesfatin-1 dose-dependently decreased gastric motility and emptying, an effect mediated by oxytocinergic neurons (Guo et al 2015). Similarly, when injected into the ARC, CeA or BMA, nesfatin-1 decreased gastric motility and emptying by exploiting the melanocortin system (Li et al 2013b, Wang et al 2014, Xu et al 2015a).…”
Section: Gastric Distension and Gastric Acid Secretionmentioning
confidence: 99%
“…Similarly, when injected into the ARC, CeA or BMA, nesfatin-1 decreased gastric motility and emptying by exploiting the melanocortin system (Li et al 2013b, Wang et al 2014, Xu et al 2015a). Strikingly, the endogenous level of NUCB2/nesfatin-1 seems to be important in the physiological regulation of gastric functions as anti-NUCB2/nesfatin-1 Ab application is also capable to alter the activity of PVN, ARC, CeA and BMA gastric distensionsensitive neurons (Li et al 2013b, Wang et al 2014, Guo et al 2015, Xu et al 2015a.…”
Section: Gastric Distension and Gastric Acid Secretionmentioning
confidence: 99%
“…Several studies have shown that nesfatin-1 plays a role in the inhibition of food intake by leading to hyperpolarization in arcuate nuclei, which is responsible for neuropeptide-Y (an orexigenic protein) secretion (7)(8)(9). Moreover, experimental studies demonstrated that increased nesfatin-1 reduces appetite by reducing gastric motility and consequently leads to malnutrition (10,11). To date, there have been two studies that investigated the relation between nesfatin-1 and childhood malnutrition and the results were conflicting (12,13).…”
Section: Introductionmentioning
confidence: 99%